2014
DOI: 10.5581/1516-8484.20140035
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of thrombocytopenia after treatment for Helicobacter pylori in a patient with immunologic thrombocytopenic purpura

Abstract: Immune thrombocytopenic purpura is the most common autoimmune hematologic disease, affecting individuals of different ages. Recently, the bacterium Helicobacter pylori entered the list of causes of immune thrombocytopenic purpura. Here we present the case of a 55-year-old female patient with low platelet counts initially attributed to chronic vaginal bleeding. As corticosteroid therapy was ineffective she was treated for H. pylori infection. Within four weeks the patient had a platelet count of 87.17 × 109/L a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
(7 reference statements)
0
5
0
1
Order By: Relevance
“…The reason for this is that H. pylori bacteria become active and exacerbate with age, as the study showed that the infection increases in males more of females, and the reason was attributed to the fact that women take antibiotics during their lifetime (pregnancy or childbirth) that may inhibit the action of these bacteria. The highest rate of infection was also recorded in rural areas, and this study does not agree with the study [21], as for the months of the year, the highest rate of infection was recorded in the months (November, March, April, and June), and it does not agree with the study [22], which showed the rainy months more An infection from the summer months, and the reason may be attributed to the fluctuation of factors that stimulate the activity and growth of H. pylori bacteria, its transmission spread،It also showed the infection rate of people dependent on household filtered water, and this reflects the chance of transmission through water contaminated with the feces of patients infected with H. pylori bacteria, and this was confirmed by [23] that is transmitted through wastewater as a result of not being treated accurately. Also, the number of casualties increased for people with low incomes, and the reason was due to the determination to provide sufficient means, whether it was food or medical, in addition to the general and personal hygiene caused by the lack of cultural awareness.…”
Section: Discussionmentioning
confidence: 64%
“…The reason for this is that H. pylori bacteria become active and exacerbate with age, as the study showed that the infection increases in males more of females, and the reason was attributed to the fact that women take antibiotics during their lifetime (pregnancy or childbirth) that may inhibit the action of these bacteria. The highest rate of infection was also recorded in rural areas, and this study does not agree with the study [21], as for the months of the year, the highest rate of infection was recorded in the months (November, March, April, and June), and it does not agree with the study [22], which showed the rainy months more An infection from the summer months, and the reason may be attributed to the fluctuation of factors that stimulate the activity and growth of H. pylori bacteria, its transmission spread،It also showed the infection rate of people dependent on household filtered water, and this reflects the chance of transmission through water contaminated with the feces of patients infected with H. pylori bacteria, and this was confirmed by [23] that is transmitted through wastewater as a result of not being treated accurately. Also, the number of casualties increased for people with low incomes, and the reason was due to the determination to provide sufficient means, whether it was food or medical, in addition to the general and personal hygiene caused by the lack of cultural awareness.…”
Section: Discussionmentioning
confidence: 64%
“…Also, Gasbarrini et al 40 showed a high prevalence of H. pylori infection in patients with ITP and reported a good response to the bacterium eradication in most of them. Several studies have also shown that H. pylori eradication in infected patients with ITP could lead to a substantial and persistent increase in platelet counts in over half of the patients treated 41 indicating the effect of the organism on the thrombocytes count. In one study the effect of H. pylori eradication on blood count results showed that; two weeks after H. pylori eradication platelet's count significantly increased 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between H. pylori infection and ITP was first described in 1998, when an Italian group reported an increase in the platelet count in 8 of 11 ITP patients treated with eradication therapy 3 . Since then, multiple studies have reported cases of eradication of H. pylori 4, 5, 6, 7, 8, 9, 10…”
Section: Introductionmentioning
confidence: 99%
“…Several theories have been proposed to explain the role of H. pylori in ITP development, including molecular mimicry between platelets and H. pylori antigens, platelet aggregation, down-regulation of the reticuloendothelial system and induction of a Th1 phenotype, which presumably favors the onset and/or persistence of ITP, but until today no proven mechanism exists, regarding the possible pathogenesis 11, 12. Currently, molecular mimicry between antigens and homology of H. pylori Urease B with platelet surface glycoprotein IIIa, leading to platelet destruction, is the most commonly accepted, but the exact mechanism is not completely understood 4, 8, 13…”
Section: Introductionmentioning
confidence: 99%